2016
DOI: 10.1007/s00109-016-1494-0
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-induced chronic dilated cardiomyopathy—the apoptosis hypothesis revisited

Abstract: The chemotherapeutic Doxorubicin (DOX) has significantly increased survival rates of pediatric and adult cancer patients. However, 10 % of pediatric cancer survivors will 10-20 years later develop severe Dilated Cardiomyopathy (DCM) and the exact molecular mechanisms of disease progression after this long latency time remain puzzling. We here revisit the hypothesis that elevated apoptosis signaling or its increased likelihood after DOX exposure can lead to an impairment of cardiac function and cause a cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 93 publications
1
27
0
Order By: Relevance
“…The present study demonstrated that doxorubicin induced apoptosis also in human normal oral keratinocytes, like that has previously been published in various cancer cells (11)(12)(13). This indicates the induction of apoptosis itself does not guarantee the anti-tumor potential.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study demonstrated that doxorubicin induced apoptosis also in human normal oral keratinocytes, like that has previously been published in various cancer cells (11)(12)(13). This indicates the induction of apoptosis itself does not guarantee the anti-tumor potential.…”
Section: Discussionsupporting
confidence: 90%
“…This points out that keratinocyte toxicity is new adverse effect of anticancer agents, in addition to cardiomyopathy (11). Further study is required to elucidate why human oral keratinocytes are more sensitive to anticancer drugs compared to human mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Irrespective of the cause of death, the dying/ dead cells must be eliminated from the myocardium, a task usually performed by macrophages. Patient 1 suffered from heart failure due to doxorubicininduced cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…With doxorubicin-induced cardiomyopathy, cardiomyocytes reportedly die via apoptosis or necrosis. [6][7][8] Irrespective of the cause of death, the dying/ dead cells must be eliminated from the myocardium, a task usually performed by macrophages. In general, however, macrophages are not frequently present within the myocardium in cases of doxorubicin-induced cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Both cardiac and lung diseases may be attributed to the increased oxidative stress, inflammation and DNA damage in the vascular cells [55] leading to apoptosis [56].…”
Section: Discussionmentioning
confidence: 99%